O comércio de bairro no pós-pandemia: competências midiáticas para o consumo local e solidário - Belmar , Patricio Isaias Lobos (2024)
Restrictions on circulation during the pandemic and the authorization from São Paulo City Hall for traders to set up decks with tables and chairs on the sidewalks after the health crisis are factors that impacted consumption in neighborhood businesses. The creation of Instagrammable spaces in establishments and the need to promote their products and services on social networks boosted the use of Instagram by small neighborhood traders, generating the need to acquire media skills to promote their businesses. This dissertation aims to verify the media skills developed by them to promote their products and services as a result of Covid-19. Theoretically based on concepts of local and supportive consumer culture, sociability practices and media literacy, this research presents a qualitative approach through in-depth interviews with those responsible for commercial establishments located on Rua Gabriele D'annuzio in São Paulo, with the in order to identify which media skills were used to handle Instagram, with the intention of increasing sales through socialization and spectacularization of the environments in the establishments. As a result of the analysis, we found that marketers responsible for using Instagram lack the necessary media skills for using the social network, as they centralize the decision-making and evaluation process, and focus on creating content that portrays their own personal experience. Another aspect verified is that, through the establishments' profile on Instagram, they seek to get closer to the identity and culture of the neighborhood through the selection and dissemination of the products and services offered. However, despite considering Instagram an important social network for business, the research finds the existence of basic media skills to access the tools, to evaluate interaction and the reach of posts, in addition to demonstrating objections to hiring people or companies specialized in the communication area that could help them enhance the use of the platform to direct their sales.